Management of selected patients with hyperprolactinaemia by partial hypophysectomy. Issue 6508 (30th November 1985) - Scanlon, M F; Peters, J R; Thomas, J P; Richards, S H; Morton, W H; Howell, S; Williams, E D; Hourihan, M; Hall, R
Abstract : Results are reported in 35 patients with prolactinomas who underwent pituitary surgery within the past five years. After surgery prolactin concentrations became normal in 26 patients and symptoms were alleviated, and nine normal pregnancies were achieved in seven women, including all those who had complained of infertility. Normal prolactin concentrations were restored in 16 of 17 patients with tumours 5-19 mm in diameter but in only six of 11 with tumours less than or equal to 4 mm and four of seven with tumours greater than or equal to 20 mm. Normal prolactin concentrations were restored in all those with preoperative concentrations below 1000 mU/l but in none of those with concentrations above 10 000 mU/l. Although not all of the patients were followed up for five years, hyperprolactinaemia did not recur in any patient whose prolactin concentration had returned to normal six weeks after surgery. This included 16 patients with macroprolactinomas (greater than 10 mm in diameter), who were followed up for from two to five years. These data contrast strikingly with those reported by others at similar stages of follow up and show clearly that partial hypophysectomy offers an acceptable alternative treatment for selected patients with prolactinomas.